تصميم وتطوير موقع للدراسات في الجزائر(التعليم الوطني - الحاج محمد لعبادي / سفيان حمادي/ يسين غنابزية (university of eloued جامعة الوادي, 2024)
أدى التطور المتلاحق والمستمر في مجال الحاسوب الآلي إلى ظهور الشبكة العنكبوتية, وقد قدم الإنفجار المعرفي العديد من الإختراعات والأشياء التي استفاد منها الإنسان المعاصر، وتعتبر الأنترنت من أهم هذه الإنجازات وأكثر الوسائل التكنولوجية المستعملة في العصر الحالي لما لها من فوائد مختلفة، ومن هنا قد سهلت الإنتقال المعلومات بين مختلف أماكن العالم بكافة تفاصيلها، وخاصة في مجال التعليم حيث سنقدم في هذا المشروع التعليمي موقع إلكتروني للتعليم الجامعي في الجزائر، حيث يحتوي هذا الموقع التعليمي على كل ما يحتاجه الطالب الجامعي من دروس وإمتحانات وأعمال تطبيقية وفيدوهات. The successive and continuous development in the field of computing has led to the emergence of the World Wide Web, and the explosion of knowledge has provided many inventions and things from which modern man has benefited. The Internet is considered one of the most important of these achievements and the most widely used technological means in the current era because of its various benefits. Here, it has facilitated the transfer of information between different parts of the world in all its details, especially in the field of education, as we will present in this educational project an electronic website for university education in Algeria, as this educational website contains everything that a university student needs in terms of lessons, exams, practical work, and videos
مدكرة ليسانس اعلام الي
Keywords: الدروس، التعليم، المعلم، الطالب; lessons; education; teacher; student